2019
DOI: 10.1002/gps.5078
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment and pain treatment for community‐dwelling people with dementia: A systematic review and narrative synthesis

Abstract: Objectives:To describe the current literature on pain assessment and pain treatment for community-dwelling people with dementia. Method:A comprehensive systematic search of the literature with narrative synthesis was conducted. Eight major bibliographic databases were searched in October 2018. Titles, abstracts, and full-text articles were sequentially screened. Standardised data extraction and quality appraisal exercises were conducted. Results:Thirty-two studies were included in the review, 11 reporting find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 89 publications
1
57
0
Order By: Relevance
“…Several studies have investigated the important association between pain and BPSD in community (10) and RACH settings, (8,(25)(26)(27) however limited research is available concerning pain in people with more severe forms of BPSD i.e. those who require specialist behaviour support, using valid instruments.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Several studies have investigated the important association between pain and BPSD in community (10) and RACH settings, (8,(25)(26)(27) however limited research is available concerning pain in people with more severe forms of BPSD i.e. those who require specialist behaviour support, using valid instruments.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…As an alternative to verbal evaluation (or self-report), a significant number of observational scales have been developed in the last 15 years. Several literature review studies describe more than 24 tools of this type14–21 and although none of the tools can be recommended based on existing evidence, several studies advocate the inclusion of any of them within a comprehensive pain care protocol 1 10 22–25…”
Section: Introductionmentioning
confidence: 99%
“…This can be challenging for individuals with limited verbal expression such as infants or with compromised cognitive ability such as individuals with dementia. A recent systematic review of pain management for community-dwelling people with dementia found that informal caregivers were more likely to report pain on behalf of the person with dementia and pain-focused behavioral observation assessment was infrequently used by practitioners [13]. Multimodal assessment of pain that includes self-reported and non-self-reported measures have been developed to capture the complexity of pain experience [14], although it is important to note that behavioral signs, effort testing, self-reported questionnaires, or symptom validity tests have been shown to be unable to identify malingering [15].…”
Section: The Struggle To Legitimize Painmentioning
confidence: 99%